E‐cigarettes effect on periodontal health: a systematic review - Wijaksana, I Komang Evan; Megasari, Ni Luh Ayu (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Smoking is well known risk factors that promote periodontal tissue destruction. Both smoking and periodontitis nowadays consider as a common health problem globally. As smoking habit evolution, electronic cigarettes (E-cigs) have emerged as an alternative to cigarettes. The number of E-cigs smoker or vaping users around the world are increasing. However, information about the effect of E-cigs on periodontium is very lacking lately. The study aimed to compare the effect of cigarette consumption on periodontium by clinical health parameters between all smokers’ type.Method: This review follows the PRISMA guidelines. Document search was carried out in PubMed, Ebsco Host and Scopus using the keywords or phrases: (periodontal health) AND (((((electronic cigarette) OR Vaping) OR e-cig) OR electronic nicotine delivery system) OR nicotine delivery system). A total of 137 articles were obtained after the duplicates were eliminated and five articles were considered met the eligibility criteria for systematic review. Result: This review found that E-cigs are less harmful compared to tobacco cigarettes, with comparable result between E-cigs smoker and non-smoker on some clinical periodontal health parameters for mean probing depth, clinical attachment loss, score of plaque index (PI) and papillary bleeding index (PBI) as well. In contrast, the study reveals that bleeding on probing level was higher among non-smokers than smokers.Conclusion: E-cigs are less harmful compared to tobacco cigarettes on some clinical periodontal health parameters. This result should be interpreted with caution because there is currently insufficient data to investigate the effect of E-cigs on periodontal health through clinical parameters.